WEB-BASED MODELING OF TRAINING ASSESSMENT SYSTEM APPLICATION OF ISLAMIC STUDENT ASSOCIATIONS - Olha Musa; Rahmawati Rahmawati; Linda Rahmawati Dunda (JSAI (Journal Scientific and Applied Informatics), 2023)
Advances in web-based information system technology motivate in building a modeling system that can facilitate the work of Islamic Student Association student organizations or commonly called HMI, is a student organization that has several levels of training or training which is basically the same as formal undergraduate education, namely Basic Training, formal education S2, namely Intermediate Training and S3 formal education, namely Advanced Training. The website-based Islamic Student Association training assessment system application was built using the PHP programming language and MySQL database with user administrator access as master data manager, and a user client created to display assessment results accessible to students. The method used is the waterfall method through the process of developing and designing a system with several stages, namely system planning to system operation and the maintenance stage. The system is designed with the PHP programming language and stored in the MYSQL database. Modeling the application of this website-based assessment system is expected to help the secretariat of the Islamic Student Association student organizations in determining the results of the election of prospective members (cadres) of the Bolmong Raya Islamic Student Association student organizations. Based on the results of system testing on the whitebox method that the calculation of V (G) = 2 and Cyclometic Complexity (CC) = 2, it can be concluded that the logic flow for the member input module carried out by the admin is effective and efficient.